Forest-based employment research: Taking stock and looking ahead - Rattiya Suddeephong Lippe; Tatiana Ojeda Luna; Doris Mutta; Jörg Schweinle (Forest Policy and Economics, 2026)

Tamarind Value Chains for Small-Scale Producers: A Review of Opportunities, Challenges, and Development Pathways - Anders Roos; Doris Mutta; Chemuku Wekesa; Marie Louise Avana; Cecilia Mark-Herbert (Ethnobotany and Economic Botany, 2026)
Tamarind ( Tamarindus indica ) is a multipurpose tree that thrives in arid and semi-arid regions worldwide and supports rural livelihoods through its ecological, economic, and cultural importance. Beyond contributing to household subsistence and income generation, tamarind products are used in traditional medicine and culinary practices, and sold in local markets. However, its market potential for small-scale producers remains underexplored. This review synthesizes evidence from 32 empirical studies, limited to those published in English between 2000 and 2024, to examine how Indigenous, traditional, and local knowledge, together with value chain dynamics, shape market opportunities for producers. The findings describe how traditional knowledge underpins the widespread use, management, and conservation of tamarind. Nevertheless, market integration is constrained by low species regeneration rates, limited processing and value-addition capacity, weak market linkages, and producers’ limited access to the end market relative to downstream intermediaries. The reviewed studies suggest that realizing tamarind’s potential as a sustainable income-generating product requires interventions that build on Indigenous, traditional, and local knowledge while improving silvicultural practices, strengthening value addition, and expanding equitable market access. Coordinated efforts among policymakers, researchers, extension services, and producers are essential to ensure that increased market participation translates into sustainable socioeconomic benefits for rural communities while supporting long-term resource management.

A horizon scan of global issues on forests and livelihoods for 2026 - Matilda Kabutey-Ongor; Katie Devenish; Mariana Hernández-Montilla; Lucas Alencar; Sandra Barragan-Contreras; Victorine Che Thöner; Reem Hajjar; Yayan Hidayat; David Kaimowitz; Birendra K. Karna; Duong T. Khuu; Anders C. Krogh; et al. (Forest Policy and Economics, 2026)

Effects of charcoal ban on value chains and livelihoods in Kenyan coast – Stakeholders’ perceptions - Chemuku Wekesa; Doris Mutta; Mahamane Larwanou; Godwin Kowero; Anders Roos (Environmental Development, 2023)